2023
DOI: 10.3390/ijerph20075402
|View full text |Cite
|
Sign up to set email alerts
|

Potential Relationship between Poor Oral Hygiene and MRONJ: An Observational Retrospective Study

Abstract: Medication-related osteonecrosis of the jaw (MRONJ) is a drug-related side effect linked but not limited to antiresorptive and antiangiogenic molecules. It recognizes several triggers in dental procedures, such as surgery, endodontic treatments, and root planing, but also prosthesis decubitus or with a spontaneous onset. Although there are many reports about the onset of this pathology, oral hygiene status is mainly described as a consequence of MRONJ. Not so much is known about the oral hygiene situation as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Additionally, in the present study, MRONJ patients presented an overall poor oral health status compared to the control subjects, as demonstrated by the higher mean score of the DMFT and prevalence of periodontal disease, which could have further impaired their OHRQoL. These findings are in line with those from other studies suggesting that poor oral health may represent a pivotal risk factor for the development of MRONJ in predisposed patients or even a worsening of osteonecrosis [46,47].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, in the present study, MRONJ patients presented an overall poor oral health status compared to the control subjects, as demonstrated by the higher mean score of the DMFT and prevalence of periodontal disease, which could have further impaired their OHRQoL. These findings are in line with those from other studies suggesting that poor oral health may represent a pivotal risk factor for the development of MRONJ in predisposed patients or even a worsening of osteonecrosis [46,47].…”
Section: Discussionsupporting
confidence: 88%
“…Studies have found bidirectional effects in the relationship between QOL and MRONJ. Specifically, low scores on Oral Health Impact Profile assessments may increase the risk of exacerbating osteonecrosis of the jaw or serve as a significant risk factor for its development [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, bisphosphonate therapy has been used to treat diffuse sclerosing osteomyelitis [ 4 , 5 ]. Unfortunately, bisphosphonates are well known to predispose patients to medication-related osteonecrosis of the jaw (MRONJ), particularly in the context of surgical, endodontic, or periodontal manipulation [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%